A genomic surveillance framework and genotyping tool for Klebsiella pneumoniae and its related species complex - Lam, Margaret M. C.; Wick, Ryan R.; Watts, Stephen C.; Cerdeira, Louise T.; Wyres, Kelly L.; Holt, Kathryn E. (Nature communications, 2021)
Klebsiella pneumoniae is a leading cause of antimicrobial-resistant (AMR) healthcare-associated infections, neonatal sepsis and community-acquired liver abscess, and is associated with chronic intestinal diseases. Its diversity and complex population structure pose challenges for analysis and interpretation of K. pneumoniae genome data. Here we introduce Kleborate, a tool for analysing genomes of K. pneumoniae and its associated species complex, which consolidates interrogation of key features of proven clinical importance. Kleborate provides a framework to support genomic surveillance and epidemiology in research, clinical and public health settings. To demonstrate its utility we apply Kleborate to analyse publicly available Klebsiella genomes, including clinical isolates from a pan-European study of carbapenemase-producing Klebsiella , highlighting global trends in AMR and virulence as examples of what could be achieved by applying this genomic framework within more systematic genomic surveillance efforts. We also demonstrate the application of Kleborate to detect and type K. pneumoniae from gut metagenomes. Klebsiella pneumoniae is a pathogen of increasing public health concern and antimicrobial resistance is becoming more prevalent. Here, the authors describe a K. pneumoniae genotyping tool, Kleborate, that can be used to identify lineages and detect antimicrobial resistance and virulence loci.